Determinants of financial performance of licensed domestic commercial banks in sri lanka - Jeyan Suganya, D.F. (University of Jaffna, 2018)
Primary objective of this study was to identify the determinants of financial performance of licensed domestic commercial banks in Sri Lanka. Data were collected from randomly selected nine licensed domestic commercial banks among thirteen listed on Colombo Stock Exchange in Sri Lanka for the period of ten years from 2006 to 2015. Return on assets (ROA) and Return on equity (ROE) have been considered as financial performance measures. Bank specific characteristics such as capital adequacy ratio, operating cost efficiency, nonperforming loans, liquidity and size as well as macroeconomic variables such as gross domestic product and interest rate have been treated as explanatory variables. Descriptive and inferential statistics have been used to examine the determinants of financial performance. The results of the study revealed that operating cost efficiency and nonperforming loans have negative and significant impact on return on assets while capital adequacy and economic growth have positive and significant impact. Further, nonperforming loans have negative and significant impact on return on equity. Finally, most of the bank specific factors have higher influence in determining financial performance of licensed domestic commercial banks rather than macro-economic factors.
Keywords: Operating cost efficiency; Non performing loans; Capital adequacy ratio; Gross domestic product; Financial performance